Three Approaches to Criticisms and Support in Evaluation of Arguments - E. N. Lisanyuk (Дискурс)
Introduction. In the article we defend a claim that criticisms and counterarguments play a more important role in modeling and evaluating arguments than defending and supporting the thesis. The novelty of this idea lies in that it shifts the main focus of the study of argumentation from the support and proof, with which it is traditionally associated, to criticism and refutation. Compared to the support and proof, criticism and refutation play more important role in the context of soft skills and communication in the practical activities, including obtaining and verifying information. The relevance of our study is dictated by the fact that argumentation is essential in both of the areas of activities, the importance of which is increasing at the present stage.Methodology and sources. We identify three ways to understanding criticism with respect to three approaches to understanding of arguments, – inferential, dialogical and abstract. The inferential view relies on verification and aims to justify a conclusion by deriving it from premises. The dialogical view sees in it the grounds offered by its author to its addressee. The author aims at achieving the latter's consent to its conclusion, and the acceptability of the arguments is verified by both justifying their conclusions and rejecting objections to them. The dialogical view relies on the principles of verification and falsification. The abstract view abstracts from the internal structure of arguments and evaluates their acceptability through the falsification, conveying the rejection of arguments in defense of the opposite conclusion.Results and discussion. The inferential view presupposes one-step criticism based on its analysis and final assessment, the dialogical one presupposes a multi-step revision of the assessment, and the abstract view implies arguments’ ability to reject counterarguments and demonstrates its role in defending the set of arguments to which it belongs protecting many arguments from criticism to which it belongs.Conclusion. In the dialogical and abstract approaches, objections and criticisms of arguments play a more important role in justifying and defending arguments than the defense and support defined by them, which play a leading role in the inferential approach to arguments.